The impacts of green Cs2ZnSi5O12:Eu2+ phosphor for white light emitting diode - Van Liem Bui; Phan Xuan Le (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
We created the green-light phosphor Cs2ZnSi5O12 (CZSO) with Eu2+ replacement for the practical use of ultraviolet white illumination through the solid-state technique. The phosphor displays many different forms and crystallizes in the space group Pbca along with Pa , with formation resembling CsAlSi2O6, the leucite in cube form. We utilized the X-ray powder diffraction as well as the spectroscopic knowledge to validate that the crystal formation in the phosphor CZSO:Eu2+ belongs to the space group Pa . CZSO can generate wide green emission with a wavelength of 504 nm when excited by ultraviolet. We enveloped the blend using the translucent silicone resin and the red-light phosphor Sr2Si5N8:Eu2+ as well as excited it using an ultraviolet light emitting diode (LED) device with a wavelength of 370 nm to generate white illumination that yields remarkable chromatic output. The generation of illumination utilizing the phosphor CZSO benefits from the wide green emission, which does not require the integration of the three phosphors that are critical to the ultraviolet pumping. Such benefit will allow the model of the apparatus to become simpler and simultaneously create a desirable ultraviolet white illumination. When the augmentation the emission efficacy as well as the heat consistency for the phosphor CZSO is realized, we can easily incorporate the ultraviolet LED devices to create better white illumination.